Fluid-Soil-Structure Interaction Phenomena on Vibration Case at Pump Station Building - Hendri Hermawan; Data Iranata; Djoko Irawan (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2019)
Excitation at low-rise reinforced concrete building had occurred within the first-year post-construction phase. It is found that the structures laying on thick soil layer while performing up to 4 kPa water transport activity. Three approaches have been adopted to investigate the dynamic behavior and the interaction the phenomenon commonly called fluid-soil-structure interaction. Applying the finite element computation to represent the dynamic of the soil-fluid and structure, existing and ideal-fixed base condition are modeled and compared each. It was found that the structure’s modes frequencies, much depend on the rigidity of the base and the fluids traffic on the pump station. Time history string of displacements at the arbitrary point shows that the vibration does occurs and it tendentious increase by time